Caecocolic intussusception mimicking appendicular lump - Devkota, Harihar; Myangbo, Suryaman; Neupane, Manik (Journal of Chitwan Medical College, 2017)
Intussusception is a rare encounter in adults. Its diagnosis can be delayed because of its long standing and non-specific symptoms and most of the cases are diagnosed on emergency laparotomy. Here, we present a case of 50 years old female who was previously diagnosed an appendicular mass, revealed caecocolic intussusception at emergency laparotomy.